Gender-specific anxiety in Jordanian EFL settings: Findings from the Foreign Language Classroom Anxiety Scale - Rababah, Luqman; Almwajeh, Motasim (East European Journal of Psycholinguistics, 2024)
This study analyzes the differing gender-based levels of anxiety that male and female students at Jadara University, Jordan, experience, utilizing The Foreign Language Classroom Anxiety Scale to highlight gender disparities in the impact of anxiety on learning. The Scale classifies the levels of students at Jadara University and decides whether or not there are statistically significant variations at the level of probability (0.05) in the levels of Foreign Language classroom anxiety among undergraduate students due to gender and the academic level of the students. For the purpose of investigating this topic in Jordan, and more specifically at Jadara University, a descriptive analysis methodology was applied to conduct an empirical investigation into the various types and levels of Foreign Language classroom anxiety on a sample of two hundred undergraduate students. When compared to their male counterparts, the female students, as suggested by the research results, exhibited much higher levels of anxiety when it came to learning a foreign language. Eventually and after conducting an analysis of the findings of the research, the searchers propose that a method of eliminating or controlling anxiety in the classroom should be implemented in order to boost the academic level of the students, as anxiety hinders learning a foreign language and affects students’ overall performance. Further, the limitations of the study as well as its relevance to English literature courses in particular and to the EFL classroom in general are evaluated and addressed. Thus, establishing a secure environment for students to engage in foreign language practice is essential for the process of language acquisition or learning. Disclosure Statement The authors reported no potential conflict of interests.